Hubungan Berat Badan Lahir Rendah Dan Gizi Buruk DenganÃÂ Angka Kematian BayiÃÂ Pada Data Survey Dinas Kesehatan Provinsi Jawa Timur - Roifah, Ifa (Jurnal Keperawatan Bina Sehat, 2012)
AbstractInfant mortality may reflect socio-economic conditions of local communities, because the baby is the age group most vulnerable to the impacts of environmental change and socio-economic. Based on BPS data, the IMR in East Java in 2005-2010 dropped from 36.65 (in 2005) to 29.99  per 1.000 live births. This figure is still far from the MDG targets by 2015S by 23 per 1,000 live births. The main causes of neonatal deaths are Low Birth Weight Babies by 29%. Other indicators of the health status remains a problem in East Java is the problem of nutritional status. In 2010 in East Java are 136 districts that are prone nutrition or 20.54% of the 662 districts in East Java Province. This study is the data that is non-reactive East Java Provincial Health Department in 38 districts. The variables in this study infant mortality, low birth weight and malnutrition. Data analysis in this study used multiple linear regression to test the method enter the 10% significance level. The test results simultaneously obtained results p value 0.000 <0.10 means that there is a relationship of LBW and poor nutrition status with infant mortality rates to the value of R2 0.415 at means 41.5% infant mortality rate caused by low birth weight and malnutrition, while 58.5% are caused by other factors . Formed regression model y = 0.275 + 0.299 LBW  + 0.207  poor nutrition status. Infant mortality rate means the unit will increase at an average of 0.299 low birth weight and infant mortality will increase at an average of 0.207 poor nutrition status predictor variables the other is constant.  Key words: Infant mortality rate, LBW and Poor nutrition status